MODELS OF THE MODERN SECULAR STATE - Merzaev I. B.; Shukrullaev Sh.Sh. (American Journals Publishing, 2023)
Many countries, with the goal of building a secular democratic state, have different approaches to the issue of creating mechanisms for the implementation of the state's attitude to religion and religious organizations. the article analyzes several models of the modern secular state from this point of view.
Keywords: State, secular, democratic, religion, religious organization, attitude, mechanism, issue, modern, secular, model.